Improvement of the concept of mitosis instruction to improve biological achievement among secondary school students - Yaki, Akawo Angwal; Sanda, Koroka Mohammed; Bello, Rabiu Mohammad (Jurnal Pendidikan Teknologi Kejuruan, 2020)
The study examined the effects of Improvised Instructional Material Enhanced Biology Achievement among Secondary School Students in Lapai, Niger State. Quasi-experimental design which involved pretest, posttest, experimental and control group. A total of eight five (85) Senior Secondary two (SSII) students randomly selected from two sampled schools formed the sample size of the study. The instrument used for data collection was a researchers’ designed Biology Achievement Test (BAT). The instrument was validated, and pilot tested and yielded a reliability coefficient of 0.75. Two research questions were raised, and two corresponding null hypotheses were formulated to guide the study, the null hypotheses were tested at 0.05 level of significant. The result of the study showed among others a significant difference in achievement score of the experimental and control groups in favor of the experimental group. The finding also showed that both male and female students’ achievements were enhanced equally. It was recommended among others that Biology teachers should be encouraged to improvise instructional materials for effective teaching and learning of Biology.